Treatment experience, burden, and unmet needs (TRIBUNE) in Multiple Sclerosis study: the costs and utilities of MS patients in The Netherlands. (July 2013) - Karampampa, Korinna; Gustavsson, Anders; van Munster, Erik Th. L.; Hupperts, Raymond M. M.; Sanders, Evert A. C. M.; Mostert, Jop; Sinnige, Okke L. G. F.; de Graaf, Jaap; Pop, Paul; Miltenburger, Carolin; Groot, Martijn T.; Relleke, Milon; et al.
Abstract Background: Multiple sclerosis (MS) is an important, highly disabling neurological disease, common among young adults in The Netherlands. Nevertheless, only a few studies to date have measured the burden imposed by MS on society in The Netherlands. Objectives: To estimate the cost and quality-of-life associated with MS in The Netherlands, while focusing on the burden of relapses and increasing disease severity. Methods: MS patients in The Netherlands (n = 263) completed a web-based questionnaire which captured information on demographics, disease characteristics and severity (Expanded Disability Status Scale [EDSS]), co-morbidities, relapses, resource consumption, utilities, fatigue and activities of daily living (ADL). Results: Most patients included in the study were receiving treatment for MS (76% of the sample). The mean cost per patient per year increased with worsening disability and was estimated at €30, 938, €51, 056, and €100, 469 for patients with mild (EDSS 0–3), moderate (EDSS 4–6.5), and severe (EDSS 7–9) disability, respectively. The excess cost of relapses was estimated at €8195 among relapsing-remitting patients with EDSS score ≤5. The quality-of-life of patients decreased with disease progression and existence of relapses. Conclusions: The cost of MS in The Netherlands was higher compared to the results of previous studies. The TRIBUNE study provides an important update on the economic burden of MS in The Netherlands in an era of more widespread use of disease-modifying therapies. It explores the cost of MS linked to relapses and disease severity and examines the impact of MS on additional health outcomes beyond utilities such as ADL and fatigue. Study limitations: Patients were selected from specialized treatment centers, therefore this sample may not be representative of the entire MS population in The Netherlands, i.e., few patients not receiving MS therapies were included. In addition, only a few patients with severe disability were included in the study sample; therefore, results for this disease severity sub-group should be interpreted with caution.